PEMANFAATAN LIMBAH ORGANIK UNTUK BUDIDAYA MAGGOT SEBAGAI PAKAN ALTERNATIF BAGI IKAN MENUJU DESA MANDIRI PANGAN - Endang Bidayani; Muhammad Mighfar; Meirisa Meirisa; Rilia Antasari; Sanja Sanja (Universitas Mataram, 2023)
Feed is the main requirement of fish farming business with production cost allocation reaching 70%. Fulfillment of feed needs can be met, among others, from factory feed, independent feed and natural feed. Maggot is an alternative high protein natural feed that can be used as aquaculture fish feed. The thematic Kuliah Kerja Nyata (KKN) in Kapuk Village, Bakam District, Bangka Regency aims to cultivate maggot as an alternative to aquaculture fish feed. Maggot cultivation media uses organic waste left over from vegetables from the local village market. The method of activity is active participation by involving Village Owned Enterprises (Bumdes) and the local community. The results of the activity, maggot cultivation was successful. Some of the products produced from maggot include live maggot, dry maggot and maggot pellets. It is hoped that the success of maggot cultivation can support the need for aquaculture fish feed to go to a food independent village.